Application of PowerPoint Media-Assisted Demonstration Method to Improve Learning Outcomes of Islamic Religious Education at Cirebon Maritim Academy - Muslih, Muhammad (PT. Riset Press International, 2024)
This study examines the extent to which the application of power point assisted by the demonstration method for Islamic religious subjects at the Cirebon Maritime Academy. This research is based on the problem of the rapid development of the technological era in the era of globalization, of course the world of education will be affected, education now must refer to the pattern of 21st century education which focuses on students to think critically and be able to use information technology. Lecturers must be able to properly apply the PowerPoint-assisted demonstration method to Islamic religious subjects. This research uses descriptive qualitative research. The purpose of this study was to find out how the application of the PowerPoint assisted demonstration method was carried out in the eyes of the Islamic religion at the Cirebon Maritime Academy. This research was conducted with the following procedures: data collection, data compaction, data presentation and drawing conclusions. Data collection techniques by observing, interviewing and documentation. The conclusion from this study is that the application of powerpoint assisted by the demonstration method by lecturers can help the student learning process, so that students can receive good learning in class. The results of this study consist of the application and support of PowerPoint-assisted demonstration methods in Islamic religious subjects. At the implementation stage it is quite good, as evidenced by the presence of lecturers who carry out learning using PowerPoint media, lecturers who actively teach using several teaching methods and lecturers who always lead discussion groups. However, the support stage is not yet perfect because the media and facilities on campus are inadequate, such as limited computers on campus, limited projector equipment in class and the current lack of electrical installations or electrical connectors in class.